Sustainable bioderived polymeric materials and thermoplastic blends made from floating aquatic macrophytes such as "duckweed". Issue 1 (7th May 2012) - Zeller, Mark Ashton; Hunt, Ryan; Sharma, Suraj
Abstract While plastics offer many conveniences to modern consumers, they represent unsustainable practices that hinder economic growth and environmental stability. Therefore, the production of biodegradable plastic from alternative feedstocks is investigated to replace conventional plastics in packaging and short‐term use markets. Duckweed represents a feedstock that elicits high biomass productivity, plus a wastewater remediation potential. To establish duckweed's potential for plastic production this study investigates the stability and thermal characteristics of plasticized and blended duckweed polymers. Duckweed biomass milled to 250 μm was plasticized using glycerol and compression molded into plastic samples. Results indicated a 3 : 1 ratio of duckweed to glycerol produced the best polymer stability. This ratio was then used to develop blends which demonstrated dispersion in biobased or polyethylene (PE) phase, except for 50% Biobased/50% PE where phase continuity was observed. Furthermore, surface morphology indicated limited homogeneity in blends and increased PE was correlated to temperature stability of biobased phase. © 2012 Wiley Periodicals, Inc. J Appl Polym Sci. 2012